Official Data Related to Religious Issues in Turkestan, Amiwdarya Department and Region - Kuwatbaevich, Jumaniyazov Damir (European Journal of Life Safety and Stability (2660-9630), 2022)
This article describes the social situation in the Amiwdarya department and region of the Turkestan region (now the region of the Republic of Karakalpakstan). The relationship between the Russian colonizers and the Soviet Bolsheviks, when religion was taken as a special issue and the ruling class was considered to be learned from the official archive information.